A Modest Proposal: How We might change the Process and Product of Managerial Research - Pfeffer, Jeffrey (Academy of Management Journal, 2007)
The article focuses on possible changes in the discipline of management science, and how the methodology and presentation of its research might be improved. The main goals of management science scholars are to reach the level of influence enjoyed by the other social sciences, especially economics, in the real world applications of their disciplines and to have more effect on actual managerial practices. London Business School has created a management innovation laboratory to collaborate with businesses on the development of improved managerial practice, and this could serve as a model for others. The methodology of academic research and scholarly publishing operate in an entirely different time frame than actual management, a difficulty that may be impossible to fully overcome. An examination of articles previously published in this publication indicate that management scientists have too often shown a preference for theoretical discussion rather than the collection of information on actual management practices and their outcomes. The huge body of knowledge created by management science in the past 50 years, however, is more than capable of being transformed into real world applications of benefit to business and society.